Exploring the nutritional status in adults with chronic schizophrenia: a cross-sectional study in Ecuador - Figueira, José Alejandro Valdevila; Ochoa, Alfonso Daniel Silva; Erazo, Luz María Valencia; Dutazaka, María Gracia Madero; Bigman, Galya; Parra, Indira Dayana Carvajal (Frontiers in Nutrition, 2025)
IntroductionSchizophrenia (SCZ) and other related factors could be associated with specific nutritional problems. Some serum biomarkers could be involved in the clinical presentation of psychotic disorders. These individuals could have significantly lower bone mineral density (BMD) and a higher prevalence of osteoporosis comparatively.ObjectiveThe purpose of our study was to assess the association of key elements of the nutritional status between patients with SCZ and other mental illnesses to promote effective treatment plans.MethodsThis was an observational, cross-sectional study with convenience sampling. The sample was divided into two groups: SCZ (S) (n = 66) and no SCZ (NS) (n = 47). We included 113 adults aged from 22 to 85 years admitted to the Institute of Neurosciences of Guayaquil (INC) residency. Anthropometric and body composition indicators were analyzed. Blood samples were collected using appropriate venipuncture techniques, ensuring aseptic conditions and minimizing hemolysis. Wilcoxon rank sum test, two-sample t test, Fisher’s exact test, and linear regression were applied to assess variables among groups.ResultsThe median BMI was 24.14 kg/m2. Visceral fat and serum creatinine were significantly higher in the S group. The prevalence of anemia, low vitamin D, low HDL, high total cholesterol, and low creatinine was 64.60, 68.14, 22.12, 10.62, and 30.97%, respectively. BMI, age, and body fat jointly influenced creatinine (p = 0.03265), while BMI and age were strongly associated with visceral fat (p < 0.001). No significant associations were found between CRP and body fat or BMI.ConclusionThe nutritional treatment in these patients should aim to prevent and treat anemia, low vitamin D, low HDL, high total cholesterol, low bone mass, and low creatinine serum levels in these groups of patients. Visceral fat and body fat percentage tend to increase with aging and should be monitored carefully. The treatment should be multidisciplinary. More studies are needed to better understand this interplay.